유방암에서 Claudin-1과 ZO-1 단백 발현 감소와 임상-병리학적 인자와의 연관성 - 김민준(Min Joon Kim); 차성재(Seong Jae Cha); 박성일(Sung Il Park); 박성준(Sung Jun Park); 장인택(In Taik Chang); 김범규(Beom Gyu Kim); 최유신(Yoo Shin Choi); 이태진(Tae Jin Lee) (Annals of surgical treatment and research, 2007)
Purpose: Tight junction proteins are either over-expressed or suppressed in some cancers. These suppressions of claudin-1 and ZO-1 protein are known to have a significant relationship with the progression of breast cancer. The authors reviewed 42 cases of breast cancer and the staining status of claudin-1 and ZO-1 in order to evaluate Claudin-1 and ZO-1 as clinicopathologic risk factors. Methods: Immunohistological staining for Claudin-1 and ZO-1 was performed in 42 post-operative pathologically diagnosed infiltrating duct carcinoma specimens. The rate of expression was compared with the clinical record, the pathological diagnosis, the estrogen receptor and progesteron receptor status and the c-erbB2 gene to evaluate the protein expression-breast cancer progression relationship and to investigate the expressions of Claudin-1 and ZO-1 as a prognostic factors in breast cancer. Results: The claudin-1 and ZO-1 expressions were both decreased in all the post-operative specimens. The claudin-1 expressions were significantly decreased 100%, 82.4% and 66.7% as the histologic grade increased. The ZO-1 expressions were shown in 44.8% of the lymph node metastasis negative group and in 7.7% of the lymph node positive group. The expression of ZO-1 decreased by 53.3%, 28.6% and 0%, with statistical significance, as the stage increased. Conclusion: The claudin-1 expressions were decreased in the poorly differentiated group, i.e., a high histologic grade, and the ZO-1 expressions were decreased in the lymph node positive group and in the high stage cancer. This shows the possibility of Claudin-1 and ZO-1 as factors for tumorigenesis and progression and as prognostic factors in breast cancer. (J Korean Surg Soc 2007;72:453-459) KCI Citation Count: 0